2018
DOI: 10.1111/bcp.13627
|View full text |Cite
|
Sign up to set email alerts
|

Moderate correlation between systemic IL‐6 responses and CRP with trough concentrations of voriconazole

Abstract: AimsVoriconazole (VCZ) exhibits wide intrapatient pharmacokinetic variability, which is disadvantageous because of its narrow therapeutic range. A considerable part of this variation remains unexplainable, despite extensive knowledge of this drug. It is hypothesized that inflammation has an impact on VCZ pharmacokinetics. In the present study, we investigated the correlation between VCZ trough concentrations and various cytokines.MethodsA prospective single‐centre analysis was performed in adult haematology pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
5
44
1
1
Order By: Relevance
“…27 Our findings showed that the increase in VCZ-C min was significantly associated with a decrease in IL-6 concentration. However, our findings differed from previous clinical study 38 whereby a positive relationship between IL-6 and VCZ-C min was observed. The clear reason for this discrepancy could not be elucidated.…”
Section: Discussioncontrasting
confidence: 99%
“…27 Our findings showed that the increase in VCZ-C min was significantly associated with a decrease in IL-6 concentration. However, our findings differed from previous clinical study 38 whereby a positive relationship between IL-6 and VCZ-C min was observed. The clear reason for this discrepancy could not be elucidated.…”
Section: Discussioncontrasting
confidence: 99%
“…Such an elevated CRP level associated risk of VRC overdose is in accordance with several previous studies reporting positive associations between elevated CRP levels and high VRC C min . This is probably related to inflammation‐induced phenoconversion, during which proinflammatory cytokines, such as interleukin‐6, reduce both CYP3A4 and CYP2C19 expression and activity .…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that hematological patients may be at increased risk of supratherapeutic VRC C min and associated toxicity when they exhibit increased CRP levels, which is very frequent for patients with IA [24,25]. Such an elevated CRP level associated risk of VRC overdose is in accordance with several previous studies reporting positive associations between elevated CRP levels and high VRC C min [15,16,[26][27][28][29]. This is probably related to inflammation-induced phenoconversion, during which proinflammatory cytokines, such as interleukin-6, reduce both CYP3A4 and CYP2C19 expression and activity [30].…”
Section: R E S U L T Ssupporting
confidence: 90%
“…Thus, other potential covariates should be tested in model building in future studies. In recent years, numerous studies have reported that inflammation, which can be reflected by the C-reactive protein levels, might influence the voriconazole trough concentration [52][53][54][55][56][57][58]. A retrospective study revealed that despite similar voriconazole doses, the trough concentrations of voriconazole in patients with severe inflammation are significantly higher than those in patients with zero to moderate inflammation.…”
Section: Discussionmentioning
confidence: 99%